Efeito toxicológico em ninfas de Nauphoeta cineria (Blattodea:Blaberidae) expostas por inalação ao 4-vinilciclohexeno - Waczuk, Emily Pansera (2019)
Exposure to numerous toxic agents, including occupational exposure to volatile organic compounds has generated numerous health problems in humans, which are correlated to the emergence of numerous diseases. The volatile organic compound 4- vinylcyclohexene (VCH) is a well-known environmental contaminant whose toxicity has been investigated due to its ovotoxic effects on various organisms. However, the mechanisms underlying its toxicity, as well as its harmful effects on other organs, are uncertain. In this study, we evaluated some signs of toxicity induced by exposure to volatilized VCH using nymphs of Nauphoeta cinerea. Nymphs were exposed to VCH by inhalation for 70 day; thereafter the headspace technique associated with gas chromatography with flame ionization detector was utilized to quantify the levels of VCH in the boxes. The survival rates, total body weight, weight of some tissues (head, fat body and reproductive organs), food and water consumption, and feces production were evaluated during the experimental period. In addition, activities of glutathione-Strasnferase (GST), acetylcholinesterase (AChE), and levels of reactive oxygen and nitrogen species (RONS) of isolated tissues were evaluated after 35 and 70 days of spontaneous exposure to volatilized VCH. The levels of volatilized VCH ranged from 3.41 to 7.03 nmol/mL. Exposure to spontaneously volatilized VCH caused a 35% reduction in the survival rate of exposed animals. Nymphs exposed to volatilized VCH for 35 and 70 days had a reduction in body weight by 1.8 and 2.6 times respectively, consequently a reduction in the head, fat body and immature reproductive organs were observed. During the period of exposure, there was also a significant decrease in food intake and feces production in the nymphs. Nevertheless, the exposure did not alter water consumption, except on the twentieth day. Moreover, GST activity increased in all the tissues evaluated after 35 and 70 days of exposure. The fat body presented the most prominent increase in GST activity, specifically after 35 days of exposure, 1.6 times larger than the control group. Exposure of nymphs to volatilized VCH also caused a significant increase in the levels of reactive species in the fat body by 1.35 and 1.47 times after 35 and 70 days respectively. However, there was no significant difference in the head AChE activity after 35 and 70 days. It is not clear if the changes in GST activity and body-weight could compromise the functioning of the tissues/organism involved due to the effects observed, which reinforces the need for further research. Therefore, our results support the harmful impact of volatilized VCH inhalation and demonstrates that the cockroach of the species of N. cinerea is a valuable model for initial toxicological screening to investigate environmental toxicants.